2001
DOI: 10.1111/j.1745-4549.2001.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-Life Evaluations of Liquid Foods Treated by Pilot Plant Pulsed Electric Field System

Abstract: There is a pressing need to validate the shelf‐life extension of Pulsed Electric Field (PEF) treated foods. This study was designed to evaluate the shelf‐lives of cranberry juice and chocolate milk as a function of PEF and the interaction of PEF+heat treatments. Cranberry juice was exposed to PEF and PEF+heat (60C), and chocolate milk to PEF+heat (105 and 112C). Microbial analysis and color measurement were performed on untreated and treated cranberry juice and chocolate milk aseptically packaged and stored at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Studies on the possibility of applying PEF in fruit juices have proliferated in recent years, concentrating mainly on apple and orange juice and other substrates of a different nature such as soymilk , apple cider (Evrendilek et al, 2000), chocolate milk (Evrendilek, Dantzer, Streaker, Ratanatriwong, & Zhang, 2001), mixed juices (Rodrigo, Martínez, Harte, Barbosa-Cánovas, & Rodrigo, 2001;Rodrigo, Barbosa-Cánovas, Martínez, & Rodrigo, 2003), model beer (Ulmer, Heinz, Gänzle, Knorr, & Vogel, 2002), horchata (Spanish beverage) (Selma, Fernández, Valero, & Salmeró n, 2003) and beer with gas (Evrendilek, Li, Dantzer, & Zhang, 2004). However, there are no studies on the application of PEF in the inactivation of microorganisms in juice-milk mixtures such as the beverage under study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the possibility of applying PEF in fruit juices have proliferated in recent years, concentrating mainly on apple and orange juice and other substrates of a different nature such as soymilk , apple cider (Evrendilek et al, 2000), chocolate milk (Evrendilek, Dantzer, Streaker, Ratanatriwong, & Zhang, 2001), mixed juices (Rodrigo, Martínez, Harte, Barbosa-Cánovas, & Rodrigo, 2001;Rodrigo, Barbosa-Cánovas, Martínez, & Rodrigo, 2003), model beer (Ulmer, Heinz, Gänzle, Knorr, & Vogel, 2002), horchata (Spanish beverage) (Selma, Fernández, Valero, & Salmeró n, 2003) and beer with gas (Evrendilek, Li, Dantzer, & Zhang, 2004). However, there are no studies on the application of PEF in the inactivation of microorganisms in juice-milk mixtures such as the beverage under study.…”
Section: Introductionmentioning
confidence: 99%
“…The PEF processing in both bench and pilot plant scale has been successfully applied to various liquid products including apple, orange and cranberry juices, and whole, 2%, skim and chocolate milk (Evrendilek, Streaker, Dantzer, Ratanatriwong, & Zhang, 2001;Evrendilek et al, 2000;Evrendilek, Zhang, & Richter, 1999;Reina, Jin, Zhang, & Yousef, 1998;Qiu, Sharma, Tuhela, Jia, & Zhang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…If shelf-life of products can be extended considerably (even when stable at room temperature), the feasibility of shipping Pasteurization of milk with pulsed electric fields 413 and marketing food products on a wider scale becomes possible, an excellent alternative for food processors and the dairy industry to consider; longer shelflife also could reduce economic losses when there is overproduction. As mentioned earlier in this chapter, some preliminary studies on PEF processing showed that the shelf-life of milk can be extended by reducing the growth rate of certain spoilage microorganisms during storage (Evrendilek et al, 2001). Chocolate milk treated under PEF (35 kV/cm; 1.4 "s pulse width; 45 "s total time) and PEF plus thermal treatment (60ëC) showed important shelf-life extension of samples stored at temperatures of 22ëC and 37ëC.…”
Section: Shelf-life Extension Of Milkmentioning
confidence: 77%
“…Chocolate milk treated under PEF (35 kV/cm; 1.4 "s pulse width; 45 "s total time) and PEF plus thermal treatment (60ëC) showed important shelf-life extension of samples stored at temperatures of 22ëC and 37ëC. When chocolate milk was stored at 4ëC, following PEF or PEF plus heat treatment, no microbial growth was detected after 197 days of storage (Evrendilek et al, 2001). Recent studies have shown that the shelf-life of milk thermally pasteurized previously, followed by PEF treatment, can extend the storage life of milk considerably.…”
Section: Shelf-life Extension Of Milkmentioning
confidence: 99%